Pengaruh Religiusitas, Personality, dan Gender terhadap Persepsi Wajib Pajak Mengenai Penggelapan Pajak - Zahro Ilmi Efendi; Eka Fauzihardan (Universitas Negeri Padang, 2023)
This study examines the effect of religiosity, personality, and gender on taxpayer perceptions of tax evasion. The sample was determined using the slovin formula and 400 WPOP samples were obtained. The type of data is primary data using multiple regression analysis. The results of this study are religiosity has a significant negative effect on the perception of taxpayers, personality has a significant positive effect on perceptions of taxpayers, and gender has no effect on perceptions of taxpayers.